Relative energy deficiency in an elite nonendurance male athlete: A case report - Zhou, Y.; Gu, N.; Wang, W.; Gao, Y.; Zhang, J. (Current Sports Medicine Reports, 2021)
Relative energy deficiency in sport (RED-S) is a well-recognized condition in women and men competing in endurance sports. However, the condition is much less common in male athletes competing in nonendurance sports. One symptom of RED-S is hypogonadotropic hypogonadism. Hypogonadotropic hypogonadism is a clinical syndrome that arises in subjects with a normal number of spermatozoa and a problem with one or more components of the hypothalamic-pituitary-testicular axis. The mechanism underlying hypogonadotropic hypogonadism is unclear. However, some have suggested that low-energy availability (LEA) plays a role. Here, we describe a nonendurance male athlete engaged in mogul skiing, which is a weight-sensitive sport. The patient presented with loss of appetite, depression, and loss of concentration after undertaking 2 months of intense endurance and anaerobic training.